2022
DOI: 10.1039/d1cp04224f
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of strontium in catalytic combustion of toluene over La1−xSrxCoO3 perovskite catalysts

Abstract: A series of LaCoO3 pervoskite catalysts substituted by Sr in A site (La1-xSrxCoO3) were prepared via a facile sol-gel method. The catalytic activity of these pervoskite catalysts for the deep...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It was found that the apparent activation energy (Ea) was consistent with the order of the catalytic performance. The CuO/TiO 2 obtained lower activation energy, indicating the catalyst could activate the toluene molecules at a lower temperature [25], which was consistent with the catalytic activity. The stability of the catalysts over time is crucial for practical applications.…”
Section: Catalytic Performancesupporting
confidence: 77%
See 2 more Smart Citations
“…It was found that the apparent activation energy (Ea) was consistent with the order of the catalytic performance. The CuO/TiO 2 obtained lower activation energy, indicating the catalyst could activate the toluene molecules at a lower temperature [25], which was consistent with the catalytic activity. The stability of the catalysts over time is crucial for practical applications.…”
Section: Catalytic Performancesupporting
confidence: 77%
“…The kinetic study was conducted under the condition of 75,000 mL·g −1 ·h −1 and 80 mg samples. The inlet gaseous concentration of toluene was set at 600 ppm in order to keep the toluene removal rate below 15%, where the effect of heat and mass transfer was negligible [ 25 ]. The activation energy (E a ) of toluene oxidation was calculated according to the Arrhenius equation (Equation (3)) as follows: where r is the reaction rate ( ), R is molar gas constant (8.314 J·mol −1 ·K −1 ), T (K) represents the reaction temperature and A is the pre-exponential factor (s −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5d, XPS peaks located near 529, 531, and 533 eV correspond to the lattice oxygen (O 2− , abbreviated as O γ ), absorbed oxygen species (O 2 2− , O 2 − , and O − , abbreviated as O β ), and the hydroxyl species and chemically adsorbed water (abbreviated as O α ), respectively. 22,56 Based on these fitting areas, the O γ /(O α + O β + O γ ) percentage slightly varies from 0.394 to 0.390 to 0.382 after cycling, demonstrating the good stability of the sample. The surface Sr element is not only located in the crystal lattice of perovskite samples (denoted as Sr lat ), but also exists in the surface phase of Sr (denoted as Sr sur ), such as the SrO phase.…”
Section: Resultsmentioning
confidence: 93%
“…The Raman spectrum of BCO is similar to that of typical brownmillerite structures such as SrCoO 2.5 and Ba 2 In 2 O 5 . [ 30 ] In contrast, the characteristic band appearing at ≈670 cm −1[ 31 ] after metal doping is attributed to the local A1g mode, [ 32,33 ] representing the oxygen stretching mode of the corner‐shared BO6 octahedra. [ 34 ] Hence, when considered alongside the XRD results, this reaffirms the cubic structure of BSC, BSVC, BSNC, and BSTC.…”
Section: Resultsmentioning
confidence: 99%